Relation Between Duration of Latent Phase of Labor and Neonatal Outcome - Faizallah, Hanan Muayad; Sarsam, Samar Dawood (Journal of Science in Medicine and Life, 2026)
Background: The latent phase of labor, marked by initial cervical changes, varies in duration and remains controversial in its management. Differences exist between nulliparous and multiparous women, with varied definitions and diagnostic criteria complicating understanding and treatment. A prolonged latent phase in labor can impact neonatal outcomes through risks like fetal distress, meconium-stained amniotic fluid, and infections, necessitating varying degrees of medical intervention for the newborn's health. Aim of the study: To determine the relation between duration of latent phase of labor and neonatal outcome. Patients and methods: This case-control study, conducted at Al-Elwiya Maternity Teaching Hospital from 1st of January 2023 to 1st of November 2023, included two hundred women in the latent phase of labor (completed 36 weeks to 42 weeks gestation). Exclusions were active labor and contraindications to vaginal delivery. Comprehensive data on maternal, labor, and neonatal variables were collected. Results: The study reported that a latent phase of labor lasting over 8 hours leads to higher cesarean sections rate, increased meconium-stained amniotic fluid, more pathological cardiotocography findings, and longer second stage of labor. Neonates born after such prolonged latent phases had lower Apgar scores at 1 and 5 minutes, indicating greater stress. These results highlight the significance of the latent phase duration in managing labor and predicting neonatal outcomes. Conclusion: The study concludes that a prolonged latent phase of labor is associated with increased risks of cesarean delivery, neonatal stress, and other complications, emphasizing the need for possible labor management.